Lipoic Acid Decreases the Expression of Poly ADP-Ribose Polymerase and Inhibits Apoptosis in Diabetic Rats - Chen J (Dove Medical Press, 2020)
Jingfang Chen,1 Qiang Li2 1Department of Endocrinology, Henan Provincial Chest Hospital, Zhengzhou, Henan Province, People’s Republic of China; 2Department of Endocrinology, Shenzhen University General Hospital, Shenzhen, Guangdong Province, People’s Republic of ChinaCorrespondence: Qiang LiDepartment of Endocrinology, Shenzhen University General Hospital, Shenzhen City, Guangdong Province 518055, People’s Republic of ChinaEmail 332706770@qq.comPurpose: To study the effects of lipoic acid on poly ADP-ribose polymerase (PARP) expression and apoptosis in diabetic rats.Materials and Methods: Sprague–Dawley rats (n=30) with high-fat diet- and streptozotocin-induced diabetes were randomly divided into two groups: diabetic model (DM) group and lipoic acid (LA) treatment group; another 10 rats were selected as normal controls (NC). The serum levels of 8-hydroxy-2ʹ-deoxyguanosine, nitrotyrosine, and 8-isoprostane; sciatic nerve cell apoptosis index; and PARP expression were detected in the rats, and morphological changes in the sciatic nerve were recorded.Results: The blood glucose level in the DM and LA groups was significantly higher than that of the NC group (P< 0.01). Compared to the NC group, the DM group showed demyelinating changes to sciatic nerve fibers. PARP expression; serum levels of 8-hydroxy-2-deoxyguanosine, nitrotyrosine, and 8-isoprostane; and the apoptosis index of sciatic nerve cells were significantly higher than those of the NC group (P< 0. 01). Following LA treatment, the above indices showed significant improvement (P< 0.01).Conclusion: Lipoic acid may improve the symptoms of diabetic neuropathy by reducing PARP activity and inhibiting apoptosis.Keywords: lipoic acid, diabetic peripheral neuropathy, poly ADP-ribose polymerase, oxidative stress, apoptosis